Design of a Palm Fruit Lifting Device for Truck - Wan, Sayyidil Athir; Mohd Azwir Azlan; Shahrin Hisham Amirnordin; Ahmad Fu'ad Idris (Research Progress in Mechanical and Manufacturing Engineering, 2026)
The palm oil farms in Malaysia are witnessing substantial expansion, particularly in the agricultural sector, which demands quicker and safer harvesting techniques. The manual lifting of palm fruit, an essential part of the harvesting process, presents inherent dangers to workers because of the physical strain. This project aims to develop a palm fruit lifting device to expedite lifting palm fruit while enhancing worker safety. The project begins with a thorough analysis of the hazards associated with manual palm fruit lifting, highlighting the prevalence of musculoskeletal disorders and the potential for serious injuries among workers. The primary goal is to create a compact, user-friendly machine capable of lifting and transporting heavy palm fruit in palm oil plantations. The study focuses on designing and developing a machine for lifting palm fruit, adhering to specific criteria: a maximum capacity of 120 kg, a manual lift height of 0.5 m below, and a lifting speed of 1 m/s. Detailed 3D models are created using SolidWorks software, which also facilitates motion analysis, simulations, and the generation of engineering drawings to ensure accuracy and functionality. The final design of the device includes anti-corrosion features. It is constructed for high durability, incorporating standardized components to ensure long-lasting performance even in challenging palm oil plantation settings. This palm fruit lifting machine is expected to surpass manual lifting methods, offering a cost-effective and efficient solution to boost productivity in palm oil harvesting practices. Ultimately, this study illustrates how the concepts of George E. Dieter were utilized to design a palm fruit lifting machine that meets industry demands. This device can potentially transform lifting palm fruit by enhancing efficiency, safety, and overall performance during harvesting.